2002
DOI: 10.1046/j.0019-2805.2001.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG4 breaking the rules

Abstract: SUMMARYImmunoglobulin G4 (IgG4) antibodies have been known for some time to be functionally monovalent. Recently, the structural basis for this monovalency has been elucidated: the in vivo exchange of IgG half-molecules (one H-plus one L-chain) among IgG4. This process results in bispeci®c antibodies that in most situations will behave as functionally monovalent antibodies. The structural basis for the abnormal behaviour of IgG4 seems to be largely the result of a single amino acid change relative to human IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
343
3
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(365 citation statements)
references
References 56 publications
15
343
3
4
Order By: Relevance
“…IgG4 has also been shown to be liable to undergo Fab arm exchange, and the presence of HCLC after running IgG4 on SDS-PAGE has been well described (15,17,18,20). The hinge flexibility and its tendency to form intra-DSBs can be limited by the introduction of S241P to the core hinge (20,21,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG4 has also been shown to be liable to undergo Fab arm exchange, and the presence of HCLC after running IgG4 on SDS-PAGE has been well described (15,17,18,20). The hinge flexibility and its tendency to form intra-DSBs can be limited by the introduction of S241P to the core hinge (20,21,30).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between IgG1 and IgG4 have also consistently shown that IgG4 molecules have lower Fab domain thermal stability compared with IgG1. IgG4 molecules are unique compared with other human IgG isotypes in that they can form functionally monovalent bispecific molecules through a mechanism called "Fab arm" or "halfmolecule" exchange (15)(16)(17)(18)(19). The interhinge DSBs at positions 239 and 242 have been shown to be liable to form intrahinge DSBs generating half-molecules that can covalently reassociate with an IgG4 half-molecule of the same or a different variable region (20,21).…”
mentioning
confidence: 99%
“…However, only large immune complexes can crosslink FccRs, thereby activating innate immune effector cells [23]. Functional monovalency might decrease the pathologic potential of IgG 4 antibodies and might, during contact with antigen, result in only small and relatively harmless immune complexes with a low potential for induction of immune activation [24]. Although anti-ADAMTS13 IgG 4 antibodies have yet to be shown to be functionally monovalent and to interfere with complement activation in vivo, it is tempting to speculate that IgG 4 autoantibodies, to some extent, act as ÔprotectiveÕ antibodies in TTP patients, inducing a milder and treatable form of TTP, whereas IgG 1 (and IgA) anti-ADAMTS13 antibodies might have higher pathogenic potential, particularly in the absence of IgG 4 .…”
Section: Discussionmentioning
confidence: 99%
“…To test whether this notion could be translated to the IgG4 sCAR design, a serine-to-proline mutation [S228P relative to the IgG4 molecule (33)] was incorporated in the IgG4 hinge to enhance interchain sCAR disulfide formation (IgG4m) (SI Appendix, Fig. S6A).…”
Section: Site and Valency Of Pne Engraftment Affects Scar-t-cell Potementioning
confidence: 99%